1999
DOI: 10.1139/v99-120
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic hydrogenation of 4-phenoxyphenol on active powders highly dispersed in a reticulated vitreous carbon electrode

Abstract: Electrodes consisting of particles of a transition metal entrapped and dispersed in a reticulated vitreous carbon (RVC) matrix were prepared in situ by stirring the particles in the presence of an RVC cathode. Such electrodes were used for the electrocatalytic hydrogenolysis (ECHsis) of 4-phenoxyphenol, a compound representative of the 4-O-5 type linkage in lignins. The electrolyses were carried out under galvanostatic control in aqueous 1 M NaOH. Raney nickel, nickel boride, and transition metals supported on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…This result can be attributed to palladium's ability to both adsorb and absorb hydrogen (17). Similarly, Dabo et al (18) observed that palladium catalysts offered maximum current efficiencies in the ECH of 4-phenoxyphenol. Palladized carbon felt was found to be an efficient catalyst for the dechlorination of 4-chlorophenol (19) and 2,4-dichlorophenoxyacetic acid (7)(8)(9); in the latter studies, current efficiencies for dechlorination reaction followed the sequence Pd > Rh > Ru catalysts.…”
Section: Dechlorination Efficiency (Table 1)mentioning
confidence: 88%
See 1 more Smart Citation
“…This result can be attributed to palladium's ability to both adsorb and absorb hydrogen (17). Similarly, Dabo et al (18) observed that palladium catalysts offered maximum current efficiencies in the ECH of 4-phenoxyphenol. Palladized carbon felt was found to be an efficient catalyst for the dechlorination of 4-chlorophenol (19) and 2,4-dichlorophenoxyacetic acid (7)(8)(9); in the latter studies, current efficiencies for dechlorination reaction followed the sequence Pd > Rh > Ru catalysts.…”
Section: Dechlorination Efficiency (Table 1)mentioning
confidence: 88%
“…At some point, we would expect a further increase in the amount of catalyst to be unproductive, due to clogging the pores of the RVC cathode; this is presumably the explanation for the lower current efficiency observed with 600 mg of catalyst. The electrocatalytic properties of various noble-metal catalysts -Raney nickel; palladium, platinum, ruthenium, and rhodium on aluminia; and palladium on calcium carbonate -were investigated ( Table 1, entries [14][15][16][17][18][19]. Catalysts on carbon powder supports were not included in the study because atrazine rapidly and strongly adsorbed to carbon powder resulting in its removal from solution without a chemical change.…”
Section: Dechlorination Efficiency (Table 1)mentioning
confidence: 99%
“…According to the literature [5][6][7][8][9][10], the overall mechanism of the electrocatalytic hydrogenation of an unsaturated organic molecule, Z=Y, on a metal/carbon supported electrode involved three steps: the formation of adsorbed hydrogen, MH ads , on the metal, the adsorption of the organic molecule on carbon, and the catalytic hydrogenation of the adsorbed organic molecule by the adsorbed hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more emphasis is placed on improving the nature of the building material of the electrodes in order to increase ECH efficiency. A variety of materials have been developed; including: Raney Ni/Ni, Raney Ni/Hg pool, Pt/Pt, Pt/C, Rh/C [7], Pt/Pt and Pt/C with different concentrations of Pt [8]; different types of composite materials incorporated in reticulated vitreous carbon (RVC) like fractal nickel (Ni), crystalline nickel boride (Ni 2 B), and metallic nanoaggregates deposited on non-conductive powders like alumina, aluminum hydroxide, barium carbonate, and barium sulphate [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Competitive reactions such as production of molecular hydrogen can also take place (steps 5 or 6). Thus, in the case of supported electrocatalysts, the matrix (inorganic powder), which supports the metallic nanoaggregates and which monitors the adsorption of unsaturated molecules, was non-conductive until now [9][10][11].…”
Section: Introductionmentioning
confidence: 99%